Uji Kemampuan Trichokompos Dalam Menekan Penyakit Layu Fusarium Pada Tanaman Tomat - Simamora, Agnes V.; Serangmo, Diana Y. L.; Iburuni, Yohanes U. R.; Widinugraheni, Sri; Hali, Antonius Suban; Abanat, Fani R. (Wana Lestari, 2022)
Fusarium wilt is one of the deadly diseases on tomato plants that need to be controlled. Trichocompost is compost containing the antagonistic fungus Trichoderma sp., which increases soil fertility and controls plant pathogens. This study aimed to examine the effect of trichocompost doses on: (1) the growth and yield of tomato plants, (2) the incidence of fusarium wilt, and (3) the severity of fusarium wilt disease in tomato plants.This research was conducted at the Laboratory of Plant Diseases and Greenhouses of Faperta Undana from March 2021 to August 2021. This study used a Randomized Block Design consisting of seven treatments repeated three times, so there were 21 experimental units. The treatments tried were Trichocompost 25 g/polybag two weeks before F. oxysporum inoculation, Trichocompost 50 g/polybag two weeks before F. oxysporum inoculation, Trichocompost 75 g/polybag two weeks before F. oxysporum inoculation, Trichocompost 25 g/polybag two weeks after F. oxysporum inoculation, Trichocompost 50 g/polybag two weeks after inoculation of F. oxysporum, Trichocompost 75 g/polybag two weeks after inoculation of F. oxysporum, andInoculation of F. oxysporum at planting without trichocompost application. The results showed that: (1) Trichocompost 75 g/polybag applied two weeks before Fusarium oxysporum inoculation was able to increase plant height, the number of leaves, and the number of tomato fruits, (2) Trichocompost applied two weeks before and after inoculation of Fusarium oxysporum was able to reduce the incidence of fusarium wilt, (3) Trichocompost 75 g/polybag, applied two weeks before Fusarium oxysporum inoculation, reduced the severity of fusarium wilt and was included in the category of high control effectiveness.